Zakatability of contemporary wealth in Malaysia / Syaharina Abdullah, Asmak Ab Rahman and Luqman Abdullah - Abdullah, Syaharina; Ab Rahman, Asmak; Abdullah, Luqman (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
Zakat institutions in Malaysia are under the state’s governance. Even though Malaysia gains its national independence 59 years ago, its zakat governance at both state and federal level seems acts as an obstacle to the system, especially in term of its uniformity in imposing fatwa on zakat including in identifying contemporary zakatable assets. This paper attempts to analyze the classical and contemporary wealth which is made subject to zakat in Malaysia and its application at state and federal levels as well as suggests ways of overcoming any obstacles associated with them. It discusses the development phases of zakatable wealth in this country and then its zakat governance at both state and federal authorities, before exploring the wealth or assets are made subject to zakat. To achieve the intended objectives, this study will be fully implemented by using the library research method based on qualitative evaluation. It involves document analyses of policy documents, journal articles, internet sources, and books. The study found that the tremendous improvement in the zakat management efficiency is because of the support from the federal government and the corporatization of zakat institutions. The study also found that there are several contemporary wealth and assets are subject to zakat made by religious authorities at state and federal levels. Among the significant zakatable wealth like various sources of personal income such as salary and remunerations, EPF, various types of business, investment, finance, and many more. The findings of this research show that zakat authorities in Malaysia accommodate contemporary changes in the concept of wealth and give an opportunity in exploring the expansion of other zakatable assets resources in the form of modern assets. However, some contemporary wealth is not clearly defined by JAKIM or JAWHAR at the federal level authority but it is adopted by some state zakat institutions.